Study of the mechanism of environmentally friendly translucent balsa-modified lysozyme dressing for facilitating wound healing - Zhou D (International Journal of Nanomedicine, 2018)
Daijun Zhou, Tao Yang, Wei Qian, Malcolm Xing, Gaoxing Luo Institute of Burn Research; State Key Laboratory of Trauma, Burn and Combined Injury; Southwest Hospital, Third Military Medical University (Army Medical University), Chongqing, China Objective: This study aimed to prepare an eco-friendly dressing using a balsa-derived membrane with lysozymes designed for antibacterial purposes.Methods: The groups included controls, balsa (group A), translucent balsa (group B), translucent balsa–lysozymes (group C), and translucent balsa-modified lysozymes (group D). Physical and chemical methods were used to characterize the materials, and the function of the materials was evaluated by in vivo and in vitro experiments.Results: Antibacterial activity against Escherichia coli and Staphylococcus aureus was ordered D > C > B ≈ A (P<0.05). Healing rates in the control, A, B, C, and D groups were 30.6%, 48.3%, 56.7%, 70.9%, and 79.2%, respectively at 7 days after injury. The lengths of new epithelia of the wound surface were ordered D > C > B ≈ A > control (P<0.05). Reverse-transcription polymerase chain reaction showed that expression of Wnt3a, β-catenin, and PCNA mRNA were ordered D > C > B ≈ A > control (P<0.05). The order of expression of PCNA was D > C > B ≈ A > control (P<0.05). There were no differences in GSK3β expression (P>0.05). The order of expression of axin was D < C < B ≈ A < control (P<0.05). The cell-migration rate at 24 hours was ordered D > C > B ≈ A > control (P<0.05).Conclusion: This translucent balsa-modified lysozyme dressing is characterized by strong antibacterial properties, stable and persistent release, no cytotoxicity, and capacity to promote antibacterial ability and epithelial growth, as well as cell proliferation and migration.Keywords: balsa, lysozyme, wound dressing, wound healing